Regenerated waste tire powders as fillers for wood fiber composites - Xu, Xinwu; Tian, Feiyu; Li, Xiaoke (Bioresources, 2020)
Waste rubber retains good elasticity and can be regenerated for use in special applications. In this research, wood fiber composites were made with waste tire powders (WTPs) as functional fillers. The physical-mechanical properties of the wood-rubber composite (WRC) panels, i.e., inner bond (IB) strength, static bending modulus (MOE), strength (MOR), and thickness swelling (TS) were assessed. The surface micro-morphology of the WRC panels was quantitatively analyzed and was graphically simulated with Matlab software. The results showed that WTPs decreased the mechanical strength and modulus of the hybrid composites, which was caused by the weak fiber/WTP interfacial adhesion. The addition of WTPs roughened the surface of composite panels. However, WRC panels showed improved hygroscopic stability and flexibility compared to pure wood fiber composites. Sanding can flatten the rougher WRC panel surface; however, it brings tiny pits to the surface that are caused by loss of rubber powders. Surface overlaying with resin impregnated paper was found to be effective to cover the tiny pits. This study showed that it is feasible to make value added rubber filled wood fiber composites with satisfactory performance.